Chromosome‐scale Salvia hispanica L. (Chia) genome assembly reveals rampant Salvia interspecies introgression - Julia Brose; John P. Hamilton; Nicholas Schlecht; Dongyan Zhao; Paulina M. Mejía‐Ponce; Arely Cruz‐Pérez; Brieanne Vaillancourt; Joshua C. Wood; Patrick P. Edger; Salvador Montes‐Hernandez; Guillermo Orozco deRosas; Björn Hamberger; et al. (The Plant Genome)
Abstract Salvia hispanica L. (Chia), a member of the Lamiaceae, is an economically important crop in Mesoamerica, with health benefits associated with its seed fatty acid composition. Chia varieties are distinguished based on seed color including mixed white and black (Chia pinta) and black (Chia negra). To facilitate research on Chia and expand on comparative analyses within the Lamiaceae, we generated a chromosome‐scale assembly of a Chia pinta accession and performed comparative genome analyses with a previously published Chia negra genome assembly. The Chia pinta and Chia negra genome sequences were highly similar as shown by a limited number of single nucleotide polymorphisms and extensive shared orthologous gene membership. However, there is an enrichment of terpene synthases in the Chia pinta genome relative to the Chia negra genome. We sequenced and analyzed the genomes of 20 Chia accessions with differing seed color and geographic origin revealing population structure within S. hispanica and interspecific introgressions of Salvia species. As the genus Salvia is polyphyletic, its evolutionary history remains unclear. Using large‐scale synteny analysis within the Lamiaceae and orthologous group membership, we resolved the phylogeny of Salvia species. This study and its collective resources further our understanding of genomic diversity in this food crop and the extent of interspecies hybridizations in Salvia.